Normative data for calcaneal broadband ultrasound attenuation among children and adolescents from Colombia: the FUPRECOL Study (2016)
Summary: Quantitative ultrasound (QUS) has been found to be a safe and reliable method for evaluating bone mineral density (BMD). Using calcaneal QUS techniques, the current study contributes to remedying this gap in the literature by establishing normative data among children and adolescents from Colombia. Introduction: Minimal data on BMD changes are available from populations in developing countries. BMD reference values for children and adolescents have not been published for a Latin-American population. The aim of this study was to establish a normal reference range of calcaneal broadband ultrasound attenuation (BUA) in Colombian children and adolescents with ages ranging from 9 to 17.9 years. Methods: A sample of 1001 healthy Colombian youth (boys n = 445 and girls n = 556), children, and adolescents (9–17.9 years old) participated in the study. A calcaneus QUS parameter (BUA) was obtained for boys and girls, stratified by age group. Furthermore, height, weight, fat mass percentage, and body mass index were measured. Centile smoothed curves for the third, tenth, 25th, 50th, 75th, 90th, and 97th percentiles were calculated using the LMS method (L [curve Box–Cox], M [curve median], and S [curve coefficient of variation]). Results: Mean (± SD) values for the participants’ anthropometric data were 12.9 ± 2.3 years of age, 45.2 ± 11.5 kg weight, 1.51 ± 0.1 m height, 19.5 ± 3.1 kg/m2 BMI, and 69.5 ± 17.1 dB/MHz BUA. Overall, all variables were significantly higher in boys except in BMI and body fat percentage. Girls generally had higher mean calcaneal BUA (dB/MHz) values than the boys, except in the age ranges 16 and 17.9, p and gt; 0.05. In addition, the BUA (dB/MHz) increased with age throughout childhood and adolescence and reached a plateau by age 15–17.9 for girls. Conclusions: For the first time, our results provide sex- and age-specific BUA reference values for Colombian children and adolescents aged 9–17.9 years. A more specific set of reference values is useful for clinicians and researchers and informs clinical practice to monitor bone mineral status. © 2015, International Osteoporosis Foundation and National Osteoporosis Foundation.